Design of magnetic shielding structure for STT-MRAM with perpendicular magnetic anisotropy by 3D simulation - Pattabiraman Lakshmipathi Subash (2018)
Magnetic Random Access Memory (MRAM) is a promising universal memory for the future due to its high-speed operation, cost effectiveness, ability to scale down in size and low power consumption. However, despite its promise, the external magnetic field can severely impact the operation of MRAM. The design of a magnetic shield to protect the device from the external field is thus of utmost importance to ensure the smooth operation of MRAM. This thesis aims to investigate the effects of materials (Mu metal, Silicon Steel and Steel 1010), gap and thickness of the magnetic shield on its shielding efficiency through computer simulations. The paper discusses shielding against the perpendicular external magnetic field for wire bond packaging type MRAM. The simulations were done using finite element method with ANSYS MAXWELL software. Silicon steel provides the best shielding for the large external magnetic field (> 400Oe) due to its high magnetic flux saturation point. In the case of low external magnetic field (< 400Oe), Mu metal has high permeability and was found to offer the most shielding as a result. The shielding efficiency of the magnetic shield can be improved by increasing the thickness of the shielding material. For example, by increasing the thickness from 0.15 mm to 0.35 mm, shielding efficiency increases around 30% for the high external applied magnetic field (> 400 oe). Extending the gap distance between the MRAM and the top shielding material was found to have a negligible effect on the shielding efficiency in the low external magnetic field but in the high external magnetic field, it shows the little percentage increase in shielding efficiency.